WATER QUALITY OF PEDID RIVER AND THE TRIBUTARIES - Jongkar, Grinang; Gabriel Tonga, Noweg; Alfred, Keleman; Cindy, Peter (UNIMAS Publisher, 2023)
The river systems flow through the Bungo Range are classified between first to third orders (Figure 4.1). The streams are mostly high gradient, narrow (range: 4.0 – 19.3 m) and shallow with rocky substrates, cool (range: 24.3 – 24.9 oC) and fast flowing water (Figure 4.2A, B, D, G). The selected water parameters i.e., dissolved oxygen and pH recorded from four stations may indicate a good quality that suitable for various usages according to National Water Quality Standard for Malaysia (NWQS) (Tables 4.1, 4.2).